Literature Review: Aspek Hukum Pelepasan Informasi Medis Kepada Pihak Asuransi di Rumah Sakit - Atina Sabelaa Husna; Julia Pertiwi; Prita Devy Igiany (Universitas Veteran Bangun Nusantara, 2025)
One function of medical records is used in the process of health financing. The health cost control mechanism that is recommended to be implemented by the government is health insurance. In the process of implementing health insurance, it is necessary to have medical information contained in medical record documents. The release of medical information that must be provided by the hospital in its implementation must comply with applicable legal regulations. In health services, especially in hospitals, the problem that often arises in releasing medical information is the use of written permission and the procedure for releasing it is not in accordance with applicable legal regulations. The purpose of this study was to identify the requirements for releasing medical information as well as procedures for releasing medical information and parties involved in the process of releasing medical information to insurers at the hospital. This research is a literature review research. The results of the SPO review for the release of medical record information to insurers at the hospital still do not guarantee the confidentiality of patient medical information as well as the parties involved are still at risk. The conclusion from this study is that 70% of the articles have used the patient's written consent/authorization optimally. As many as 90% of the articles already have SPOs regarding the release of medical information which are applied in each hospital. As many as 100% of articles involve parties that must be present, namely the applicant consisting of patients or insurers, doctors, and medical record officers. Keywords: Legal Aspect, Insurance, Release of Information